2016
DOI: 10.1111/jch.12775
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Uncontrolled Blood Pressure in Treated Hypertensive Individuals: First Population‐Based Study in Lebanon

Abstract: Arterial hypertension is a leading risk factor for cardiovascular disease and stroke. This study aimed to assess the predictors of uncontrolled systolic and diastolic blood pressure (BP) in Lebanon among treated hypertensive individuals. The authors included 562 participants 40 years and older. The potential predictors included sociodemographic characteristics, self-reported health information, and medication adherence. Prevalence of uncontrolled systolic and diastolic BP reached 43.1% and 24.9%, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
4
19
1
1
Order By: Relevance
“…In this study, the prevalence of uncontrolled hypertension is 52.7%, which is almost consistent with studies done at Gondar University Hospital, in northwest Ethiopia, Lebanon, USA, and reported as 53.4%, 51.1%, and 54%, 8,10,26 respectively. However, it is lower compared to study done in Singapore, and two different health institutions in Nigeria, which was reported as 62.3%, 62.3%, and 75.8%, respectively, 27,28 and this difference might be due to difference in study population (community vs hospital-based study) in Singapore and the difference of urbanization, which is more in Nigeria than Ethiopia and mainly because of discrepancies in environmental factors and lifestyle behaviors such as feeding habits and sedentary lifestyles that bring hypertension to be difficult to control.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the prevalence of uncontrolled hypertension is 52.7%, which is almost consistent with studies done at Gondar University Hospital, in northwest Ethiopia, Lebanon, USA, and reported as 53.4%, 51.1%, and 54%, 8,10,26 respectively. However, it is lower compared to study done in Singapore, and two different health institutions in Nigeria, which was reported as 62.3%, 62.3%, and 75.8%, respectively, 27,28 and this difference might be due to difference in study population (community vs hospital-based study) in Singapore and the difference of urbanization, which is more in Nigeria than Ethiopia and mainly because of discrepancies in environmental factors and lifestyle behaviors such as feeding habits and sedentary lifestyles that bring hypertension to be difficult to control.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, the multivariate analysis showed that men had 32% lower odds of having controlled BP. This finding aligns with those of other studies . As a variable, sex is intrinsically associated with other behavior (eg, increased demand for health care, differing rates of adherence to treatment, and alcohol consumption) and factors (eg, abdominal obesity, metabolic syndrome) that could be associated with BP control.…”
Section: Discussionsupporting
confidence: 90%
“…Despite tobacco being confirmed as a classic risk factor for CVD, no significant association was found between tobacco and BP control in our study. Similar results have been found in ALLHAT and in a Lebanese study . Finally, history of CVD was associated with higher odds of having controlled BP, consistent with results from ALLHAT …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations